The call for Malaysia to revive its national ego - Abdul Razak, Mohd Abbas (Kulliyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS), IIUM, 2021)
In our day-to-day conversation, ego explains the state of the behaviour of someone who is being proud, pompous, arrogant, never felt defeated, etc. While egotism, egocentrism and big fat ego, explain one being self-centred, selfish and not bothered about the common good of the society. Diametrically opposite to the preceding meanings, ego in psychology and philosophy is referred to one’s identity, inner qualities, personality, the ‘Self’ or the ‘I-am-ness’ of an individual. Compared to the physicality of a thumbprint, ego is something intangible but it explains the quality of that entity being in existence and alive. Iqbal (1877-1938) the philosopher says that the ego is the ‘life force’ within a living organism that leaps to the external world to indicate its existence. Metaphorically it explains the action of an organism that tries to say that “this is me and I exist and need to be respected”. More to say, that individual ego is trying to show its uniqueness and for that matter, it has its own pride and dignity. As such, it demands to be respected. Since the focus of this article is not centred on the mystic understanding of ego, we would rather leave such a discussion for another time.